Estrategias de enfrentamiento (coping) en personas ostomizadas - Barnabe, Natalia Campos [UNESP] (2008)
This study aimed at understanding the experience of individuals with intestinal diversions as regards coping with their new life conditions. The qualitative approach was used, involving 11 ostomized subjects. The data were collected by means of semi-structured interviews which were taped and later fully transcribed and analyzed according to Content Analysis as proposed by Bardin and the Coping theoretical framework . The findings in the study were evidenced by three core categories denominated: i did not choose it; i had to accept it and i have to live with the ostomy. The form to manage the condition of being ostomized was revealed by coping strategies which were based on both emotions and the problem itself. The study contributed for reflection and application of knowledge in assistance practice and teaching for care the ostomized.